SUSTAINED-RELEASE PERMANGANATE (REMOX® SR ISCO REAGENT) AND PERSULFATE FOR PASSIVE TREATMENT OF CHLORINATED SOLVENTS AND EMERGING CONTAMINANTS - J. DUGAN, PAMELA; NEGRÃO, PAULO (Águas Subterrâneas, 2013)
A sustainable, simple, and low O&M approach has been developed using innovative oxidation chemistries in concert with innovative slow-release deployment strategies to achieve passive, cost-effective treatment of large chlorinated solvent and emerging contaminant plumes. This novel remedial technology involves oxidants in the form of sustained-release permanganate and sustained-release persulfate. Paraffin wax is used as the environmentally benign and biodegradable matrix material for encapsulating solid potassium permanganate (KMnO4) or sodium persulfate (NaS2O8) particles. Sustained-release (SR) oxidants contain 80% permanganate or unactivated persulfate and can be formed as cylinders for direct push applications, inserted into holders for emplacement in permanent or temporary wells. The material may also be chipped/cubed for hydro-fracturing into low permeability media for treating back diffusion of organic contaminants. This presentation will provide the results of a variety of experimental and modeling efforts as well as preliminary results from RemOx® SR ISCO Reagent pilot-scale field studies.